Особливості визначення характеристик статичної міцності металів і сплавів при температурі 4,2 К - Новогрудський, Леонід Семенович; Зенкін, Микола Анатолійович; Майборода, Олександр Петрович (Eastern-European Journal of Enterprise Technologies, 2009)
Considered and analysed main positions of standards of АSТМ, ISO and GOST, which set the method of tests of materials on tension at the temperature of liquid helium. The main are certain, which regulate the parameters of deformation, loadings and sizes of standards at the test of metals and alloys in the conditions of the indicated temperature. Recommendations are given in relation to additions of positions of standards.